Memperkuat Potensi Desa Melalui Capacity Building Badan Usaha Milik Desa (BUMDES) Kedungturi Kecamatan Taman Kabupaten Sidoarjo - Risa Kharisma; Susi Hardjati (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Sidoarjo Regency is one of the districts in East Java Province that continues to strive to develop and develop village potential through the establishment of BUMDes. The government continues to encourage that every village has BUMDes which can later be a driver in increasing the potential of the village. BUMDes in Kabupaten Sidoarjo has three categories, namely advanced, developing, and beginner categories. One of the advanced category BUMDes in Sidoarjo Regency is BUMDes Surya Sejahtera which is located in Kedungturi Village, Taman District. In the success of its management, it can be known the positive impact for the government and the people of Kedungturi Village. The purpose of this research is to describe the capacity development of BUMDes in increasing the potential of Kedungturi village, Taman District. This research method uses descriptive qualitative with data collection methods through interviews, observations, and documentation. Data analysis in this study through data collection, data condensation, data presentation and drawing conclusions. The results of the research show that the capacity development carried out by BUMDes Surya Sejahtera in the aspects of resources and managerial has been running well and in accordance with the existing theory, but further capacity development is still needed from the aspect of technological resources and cooperation relations.